PEMAHAMAN KONSEP MATEMATIKA SISWA SMP MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH - Aprilia Sari (Departemen Matematika, 2018)
Understanding of mathematical concepts is one of goals that must be mastered by students in learning mathematics. However, based on thefact, understanding of mathematical concepts ability of students grade VIII SMPN 16 Padang is still low. One effort that can be done to over come this problem is by applying cooperative learning model make a match type. The purpose of this study is to describe whether the understanding of mathematical concepts of students wholearn with cooperative learning modelmake a matchtype is better than conventional learning. This research’s type is quasi experiment with static group design. Based on data analysis using t-test, it is obtained that P-Value = 0,000 < α = 0.05, then reject H0. Thus, it can be concluded that understanding of mathematical concepts of students using cooperative learning model make a match type is better than conventional learning. Keywords – Understanding of mathematical concept, make a match, conventional learning